Potential economic effects of TTIP for the Netherlands and the EU - Rojas-Romagosa, Hugo (Brussels, 2016)
"The Transatlantic Trade and Investment Partnership (TTIP) is a comprehensive preferential trade agreement that is expected to have a significant effect in EU and US bilateral trade and investment relations. As the negotiations are ongoing, this paper uses a scenario analysis to estimate the potential effects of TTIP under likely negotiated outcomes. In our main scenario, we assume a final trade deal where current tariffs are eliminated and non-tariff barriers are significantly reduced. Using a CGE model (WorldScan), we simulate the potential economic effects for the Netherlands and the EU. We find that US-Dutch bilateral trade doubles and this is translated into a positive but moderate effect on income of 1.7% for the Netherlands by the year 2030. These potential gains are higher than those for the EU and the US (both around 1%)."